Strategic forest management options for small-scale timber harvesting on Okinawa Island, Japan - Jemali, N.J.N.B.; Shiba, M.; Zawawi, A.A. (Springer Link, 2015)
Forest-related activities are important as the economic and social drivers for local residents in Okinawa Island. Therefore, strategic timber management planning is a prerequisite to achieve a sustainable timber yield and optimize forest resource utilization. In this study, the practicability of the Timber Harvest Simulation Model (HARVEST) developed by Eric Gustafson from USDA was tested with the aim of assessing the spatial pattern consequence of timber management plans in the subtropical Yambaru Forest of Okinawa Island. HARVEST evaluates options for timber harvesting by providing comparable predictions of age effect, forest spatial distribution and forest edge habitat, as well as patch structure in a targeted forest type and management area. The timber harvest simulation in 2.1 % of the Yambaru timber production areas was investigated using two alternative cutting methods (clustered and dispersed). It was found that small-area clear-cut harvesting, mimicked by a clustered method, was the practical harvesting practice in Yambaru with an estimated timber volume 12 % higher than that from the selective-logging mimicked by the dispersed method. The mean patch size of the harvested area and forest edge habitat were significantly correlated with timber harvesting method. In spite of some limitations quantified in the model, information generated from HARVEST model was applicable and practical for many forest stakeholders and effective for time-and-cost consideration.